Difference Effect of The Combination of Lavender Aromatherapy and Effluerage with Breathing Relaxation on Pain Intensity During Labor among Primiparas - Murtiningsih M; Shintya Tri Andani (Ikatan Perawat Maternitas Indonesia Provinsi Jawa Barat, 2018)
Although labor pain is a physiological process but it was feel severe and longer for primiparas. Because of a cervical effacement earlier than dilation, and no experience of labor can affect women feel anxiety and fear of labor process, it cause increasing of pain. The non-pharmacological method was cheaper, simple, effective, and no side effect can help women to control of labor pain by herself or another person. The combination of lavender aromatherapy and effleurage can increase of relaxation of uterus contraction and between of it, so labor pain decreasing. The aim of this study was to determine difference effect of the combination of lavender aromatherapy and effleurage with breathing relaxation on pain intensity during labor among primiparas. This study used pre-experiment design with Pretest – Post-test Control Group design. The consecutive sample of 32 laboring women divided to two groups of the intervention and control group. The pain scale measured by NRS questionnaire. The results showed that mean of pain scale before being given intervention is 7.25. It was the same of two groups. The average of pain scale decreasing to 5.25 in the intervention group and to 6.25 in the control group. The result of t-test dependent obtained p-value = 0.000, so meaning that two of interventions was able to decrease of the labor pain. The result of t-test independent obtained p-value 0.004, so meaning that there was significantly difference of pain scale during labor of the intervention group to compare with control group. Suggested to health care who provide services at labor room to give a combination of lavender aromatherapy and effleurage as a non-pharmacology therapy alternative besides breathing relaxation to decrease of pain labor in primiparas.Keywords: Aromatherapy, Labor, Massage, Pain, Relaxation